The aerodynamic interference effects of side walll proximity on a generic car model - Strachan, R K (Department of Aerospace, Power & Sensors, 2010)
The flow around a generic car model both in isolation and in proximity to a near side wall has been investigated utilising experimental and computational methods. Phase one of this investigation tested a range of Ahmed generic road vehicle models with varying backlight angles in isolation, employing laser-Doppler anemometry, static pressure and aerodynamic force and moment measurements in the experimental section. Additionally, numerical simulations were conducted using a commercial Reynolds-averaged Navier Stokes (RANS) code with the RNG k-ε turbulence model. This phase served both to extend the previous knowledge of the flow around the Ahmed model, and analyse the effects of both the supporting strut and rolling road. Phase two then used similar methods to investigate the Ahmed model in proximity to a non-moving side wall. Results from phase two are compared with previous near-wall studies in order that an understanding of the effects of wall proximity can be presented, an area lacking in the existing literature. It is found that the flow on the isolated model must be understood before the effects of side wall proximity can be assessed. There is though, in general, a breakdown of any longitudinal vortices on the near-wall side of the model as model-to-wall distance reduces, with an increase in longitudinal vortex strength on the model side away from the wall. There also exists a large pressure drop on the near-wall model side, which increases in magnitude as model-to-wall distance reduces, before dissipating at separations where the boundary layer restricts the flow. Additionally, there is found to be a pressure drop on the top and bottom of the model with decreasing wall distance, with the relative magnitudes of these dependent on model geometry.